2013
DOI: 10.7860/jcdr/2013/6980.3526
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Efficacy of Gingival Retraction using Polyvinyl Acetate Strips and Conventional Retraction Cord – An in Vivo Study

Abstract: Statement of Problem:A new material is proposed in dentistry in the form of strips for producing gingival retraction. The clinical efficacy of the material remains untested. Purpose of the Study:This study aimed to determine whether the polyvinyl acetate strips are able to effectively displace the gingival tissues in comparison with the conventional retraction cord. Material and Methods:Complete metal ceramic preparation with supra-gingival margin was performed in fourteen maxillary incisors and gingival retra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…77% were aware of retraction cord. Shivasakthy et al, (Shivasakthy, 2013) also found in their study that most of the dentists were aware of the retraction cords. Also xhonga FA and Kannan A(xhonga, 1971;Kannan and Venugopalan, 2018) found similar results.…”
Section: Resultsmentioning
confidence: 82%
“…77% were aware of retraction cord. Shivasakthy et al, (Shivasakthy, 2013) also found in their study that most of the dentists were aware of the retraction cords. Also xhonga FA and Kannan A(xhonga, 1971;Kannan and Venugopalan, 2018) found similar results.…”
Section: Resultsmentioning
confidence: 82%
“…Only eleven studies satisfied the inclusion criteria for this systematic review. One study was later excluded on the basis of its quality, as the results were inappropriately reported. The authors of that study were consulted for clarification of the results, but no response was received.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 In the present study, all the gingival retraction systems caused gingival displacement of more than 0.22 mm, which is the optimal displacement required for recording of gingival finish lines. 10 Hence, all the three gingival retraction systems are effective for gingival displacement. However, laser retraction system was the most effective among the three and least amount of displacement was caused by magic foam.…”
Section: Jcdpmentioning
confidence: 99%